Impact of Principals’ Leadership Styles on Truancy Among Students of Public Secondary Schools in Zamfara State Metropolis, Nigeria - U. Sidi, Abdulhakeem; M. Abubakar, Hamza; G. Danmaitaba , Suleman (Kashere Journal of Education, 2021)
This study aimed at investigating impact of principal’s leadership styles on truancy among students of public secondary schools in Zamfara metropolis. Two objectives guide the conduct of this study. Descriptive survey design was adopted. The target population of the study consists of all the teachers and students in public secondary schools in Zamfara metropolis. Stratified sampling technique was employed in selecting 30 schools from two strata (Public and Private) Likewise, 160 teachers out of 1874 teachers and 320 students out of 13,789 students across 30 public secondary schools were selected using Krejcie and Morgan, (1971) table of determining the sample size required for the study. The instrument used for the study was self-structure questionnaire which was entitle “Perception of Principals Leadership Styles on Students Truancy Questionnaire in Senior Secondary Schools” (PPLSSTQSSS). The instrument was validated by two experts from the Department of Educational Foundations, Faculty of Education, Federal University of Kashere. In testing the reliability of the instrument pilot study was conducted in none of the sample schools not covered by the study, Cronbach Alpha of reliability was employed and a reliability coefficient index of 0.75 was obtained. Data were analyzed using descriptive statistics. The findings of the study showed that truancy was a problem experienced in all the schools under study. Democratic leadership styles were popularly used by the principals in Zamfara metropolis. The various leadership styles employed by various principals had a great impact on truancy. Autocratic leadership style was found out to be associated with harshness and leaders who practice this style of leadership are always distant from teachers and students. The study concluded that truancy was caused by factors such as inability to cope with academic pressure, dislike for the school environment caused administration techniques used by school leadership, lack of school fees, sickness, problems related to family background. The study recommended awareness campaign among school administrators to enhance their understanding on the circumstances in which each leadership style is appropriate. The study also recommended wide adoption of democratic and charismatic leadership styles in curbing the rising cases of truancy among learners.